(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
This paper deals with interim relief after the modification brought by Law 13.105/15, better known as the New Civil Procedure Code, and the stabilization of its effects. It can be said that it is an application prior to the formulation of the request for definitive guardianship and aims to advance its effects. In fact, it may become capable of stabilizing the effects of the guardianship, that is, that concession initially made by the judge, may be consolidated in time, when the procedures that make such stabilization possible are verified. To this end, this paper will be divided into two topics. Briefly, it is anticipated that the first one will analyze the institute of anticipated relief in the Brazilian legal system, in light of the legal and doctrinal changes brought about by the New Civil Procedure Code of 2015. In the second moment, we seek to face the central issue of this research, regarding the stabilization of the preliminary injunction requested in antecedent character, in view of the obstacles created by the legislation itself, as verified in article 303, §1, I of the Code of Civil Procedure.